OCURRENCIA, DISTRIBUCIÓN Y ABUNDANCIA DEL GÉNERO PASSERINA EN LA RESERVA DE LA BIOSFERA LA SEPULTURA, CHIAPAS - Altamirano González Ortega, Marco Antonio; Martin Gómez, Martín Francisco; Cartas Heredia, Gerardo De Jesús (Instituto de Ecología, A.C., 2002)
The study of four species of birds of genus Passerina in the Biosphere Reserve La Sepultura, Chiapas, Mexico was carried out. The objective was to know the ocurrence places and to estimate their distribution and abundance. The search consisted on carrying out the summary of current and historical records in databases and the sampling in six sites that were visited during January to December of 1999. All records were assigned to a coordinate system, being also digiized the distribution of types of vegetation and the gradient altitudinal of the study of area. By means of analysis of averlaps of these coverings and the reported ecological tolerances and observed for the species, three maps were generated: one of the ocurrence of the four species and other two on the areas of potential distribution, for the species residents. The relative abundance was obtained by season (dry and humid) for each one of the species of the genus, with relationship to the sampling effort and expressed in percentage for each site. The results of abundance were analyzed by the statistical test of G. The sites of ocurrence of the species of the genus are in five municipalities in those that the Reserve is located. The resident species are restricted to the distribution of Tropical Semi-Deciduous Forest. The migratory species presented a wide distribution range, being able to inhabit pine forest, pine-oak forest and cloud forests. The abundance of the species of the genus, it was greater in the nearby region to the Isthmus of Tehuantepec.